APLIKASI METODE ROTATED GUMBEL COPULA UNTUK MENGESTIMASI VALUE AT RISK PADA INDEKS SAHAM PASAR ASIA - AKBAR, IKHSAN; DHARMAWAN, KOMANG; ASIH, NI MADE (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p255, 2019)
Value at Risk is a tool used to calculate the value of risk in investing. The purpose of this study was to estimate VaR in the portfolio using the rotated Copula Gumbel approach, which originated from the Archimedean copula family. Copula can provide an overview of the relationship between random VaRiables on a quantil scale which is very useful in explaining the interrelationships in extreme events. This VaR calculation is used in portfolios from the Indonesian stock index (JKSE), Malaysia (KLSE), Singapore (STI), and South Korea (KOSPI), in the period of June 1, 2016 to June 1, 2018 (519 data). VaR is calculated using a daily period with a confidence level of 99%. So that the VaR of each portfolio is obtained, JKSE-KLSE is 1.41%, JKSE-STI is 1.38%, JKSE-KOSPI is 1.39%, KLSE-STI is 1.44%, KLSE-KOSPI is 1.42%, KOSPI-STI is 1.48%. The highest risk level that can be derived from the portfolio contains a combination of the Singapore stock index (STI) and the South Korean stock index (KOSPI).